2021
DOI: 10.1021/acs.jpcb.1c03619
|View full text |Cite
|
Sign up to set email alerts
|

Beating Heart of Cytochrome c Oxidase: The Shared Proton of Heme a3 Propionates

Abstract: Cytochrome c oxidase (CcO) pumps protons from the N-side to the P-side and consumes electrons from the P-side of the mitochondrial membrane driven by energy gained from reduction of dioxygen to water. ATP synthesis uses the resulting proton gradient and electrostatic potential difference. Since the distance a proton travels through CcO is too large for a one-step transfer process, proton-loading sites (PLS) that can carry protons transiently are necessary. One specific pump-active PLS couples to the redox reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Analyzing the conformation changes in MD simulation trajectories of His376Phe and His376Tyr, it was discovered that there is consistently a hydrogen-bonded water molecule between PRAa 3 and PRDa 3 . 71 This leads to two distinct possible paths for the proton transfer, one of which involves the stable water molecule between PRAa 3 and PRDa 3 (Fig. 6(D) and (F)), while the other does not (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Analyzing the conformation changes in MD simulation trajectories of His376Phe and His376Tyr, it was discovered that there is consistently a hydrogen-bonded water molecule between PRAa 3 and PRDa 3 . 71 This leads to two distinct possible paths for the proton transfer, one of which involves the stable water molecule between PRAa 3 and PRDa 3 (Fig. 6(D) and (F)), while the other does not (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The initial protonation pattern ( Supplementary Table S1 ; SI) was determined based on the initial model [HoxG from the crystal structure 3RGW ( Fritsch et al, 2011 ) with modelled N-terminal Strep-tag II as a random coil, Figure 1 ], by computing pK A values with Karlsberg2 + (KB2 + ; Rabenstein and Knapp, 2001 ; Kieseritzky and Knapp, 2008 ; Meyer and Knapp, 2015 ), as in previous applications ( Wolf et al, 2020 ; Dragelj et al, 2021a , b ; Batebi et al, 2018 ). The pK A values have been computed in the range from −10.00 to 20.00, not only for the starting model but also for the structures from GaMD trajectories obtained every 2 ns.…”
Section: Methodsmentioning
confidence: 99%
“…Following this interpretation, the water cavity above the heme cofactors [46,57] would possibly connect their propionic acid moieties through a hydrogen-bonding network. It has been suggested that the propionic acids of heme a3 "store" a proton [101], making the whole hydrogen-bonding network a candidate for the PLS. A similar concept has been discussed for the transmembrane proton pump bacteriorhodopsin, where two glutamic acid residues share a proton to form a "intermolecular proton bond" acting as the proton release group [102].…”
Section: Changes Of Other Amino Acid Residuesmentioning
confidence: 99%